Diaspora, development, and democracy: the domestic impact of international migration from India - Kapur, Devesh (Princeton University Press, 2010)
What happens to a country when its skilled workers emigrate? The first book to examine the complex economic, social, and political effects of emigration on India, Diaspora, Development, and Democracy provides a conceptual framework for understanding the repercussions of international migration on migrants' home countries.